2022
DOI: 10.1155/2022/9458646
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Newly Diagnosed Prediabetes and Diabetes with Cognitive Function among Chinese Adults Aged 45 Years and Older

Abstract: With population aging, diabetes mellitus and cognitive function decline are common health problems among older adults worldwide. This longitudinal study is aimed at estimating the longitudinal associations of newly diagnosed prediabetes and diabetes status with cognitive function among Chinese adults aged 45 years and older and evaluating the clinical risk factors associated with cognitive function. Data were obtained from the China Health and Retirement Longitudinal Study (CHARLS). A total of 8716 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…One systematic review (28) suggest there is insufficient evidence to support a connection between prediabetes and cognitive impairment, while another meta-analysis reported that there was moderate-to-high-quality evidence of a positive association between prediabetes and dementia (29). An 8-year longitudinal study also found no significant association between baseline prediabetes status and later cognitive function (30). Further research with larger sample sizes is needed to better understand cognitive impairment in prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review (28) suggest there is insufficient evidence to support a connection between prediabetes and cognitive impairment, while another meta-analysis reported that there was moderate-to-high-quality evidence of a positive association between prediabetes and dementia (29). An 8-year longitudinal study also found no significant association between baseline prediabetes status and later cognitive function (30). Further research with larger sample sizes is needed to better understand cognitive impairment in prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were selected based on previous studies for their potential association with diabetes and cognitive function 16,17 . They included age (year), sex, marital status (married or cohabitated, widowed, other status), physical activity (based on short form of the International Physical Activity Questionnaire, 18 only half participants were randomly chosen to answer these questions), level of education (no formal education, middle school education and high school education and above), living in rural or urban area, current smoking status (still have the habit of smoking vs. have quitted smoking or non‐smokers), current alcohol drinker (yes/no, drink any alcoholic beverages in the past year), body mass index (BMI, kg/m 2 ), dyslipidaemia (total/high density lipoprotein (HDL) cholesterol ratio), high‐sensitivity C‐reactive protein (CRP), depression (defined as the 10‐item Center for Epidemiological Studies Depression Scale of 10 or greater, range 0–30) 19 and self reported hypertension, heart disease and stroke by asking ‘Have you been diagnosed with [conditions listed below, read one by one] by a doctor?’…”
Section: Methodsmentioning
confidence: 99%
“…Covariates were selected based on previous studies for their potential association with diabetes and cognitive function. 16,17 They included age (year), sex, marital status (married or cohabitated, widowed, other status), physical…”
Section: Covariatesmentioning
confidence: 99%